2022
DOI: 10.1002/bsd2.227
|View full text |Cite
|
Sign up to set email alerts
|

The role of community involvement in sustainable tourism strategies: A social and environmental innovation perspective

Abstract: Social innovation and environmental innovation is a fast-growing phenomenon. More and more businesses are trying to understand how social and environmental innovation can help their business model. The purpose of this paper is to examine the contribution of community involvement toward social and environmental innovation to achieve sustainable tourism development. Perceptions of 650 local community members of different tourist destinations of Jammu and Kashmir have been used to meet the objectives of the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 66 publications
2
18
0
Order By: Relevance
“…This article's contribution to the literature is developing a business strategy and concept that rethinks their specificities in the new markets of tomorrow. The article also confirms ongoing analyses (Bagul et al, 2023;Patil & Vhavale, 2023;Setiarini et al, 2023;Sharma & Bhat, 2023)…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This article's contribution to the literature is developing a business strategy and concept that rethinks their specificities in the new markets of tomorrow. The article also confirms ongoing analyses (Bagul et al, 2023;Patil & Vhavale, 2023;Setiarini et al, 2023;Sharma & Bhat, 2023)…”
Section: Discussionsupporting
confidence: 83%
“…This article's contribution to the literature is developing a business strategy and concept that rethinks their specificities in the new markets of tomorrow. The article also confirms ongoing analyses (Bagul et al, 2023; Patil & Vhavale, 2023; Setiarini et al, 2023; Sharma & Bhat, 2023) on the issues of business strategy and development. Based on the research results, it is a clear and undeniable fact that business strategy and development are determined by three fundamental factors: viral threat, digitalization, and sustainable development.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…It creates jobs and reduces the level of youth unemployment. It engages local populations and stakeholders in the developmental processes (Sharma & Bhat, 2022). Due to the eagerness to attract tourists, governments of all nations are trying to improve the level of infrastructural development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the same way, Bartlett and Preston (2000) and Wood (1984), concluded that socially responsible business activities reduce conflicts between stakeholders and firms, which ultimately improve the financial performance of firms. Sharma and Bhat (2023) investigated social and environmental innovations and business performances. They found that social and environmental innovations through community participation have a positive impact on sustainable tourism development and business performance.…”
Section: Review Of Literaturementioning
confidence: 99%